1993
DOI: 10.1152/ajplung.1993.264.2.l116
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia reduces potassium currents in cultured rat pulmonary but not mesenteric arterial myocytes

Abstract: To explore possible mechanisms underlying hypoxia-induced pulmonary vasoconstriction, the effect of hypoxia on outward K+ current (Iout) was evaluated in primary cultured rat pulmonary (PA) and mesenteric (MA) arterial smooth muscle cells using the whole cell patch-clamp technique. When the cells were bathed in standard physiological salt solution and the patch pipettes contained Ca(2+)-free media with 10 mM ethylene glycol-bis(beta-aminoethyl ether)-N,N,N',N'-tetraacetic acid (EGTA), virtually all of the Iout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
229
2
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(249 citation statements)
references
References 27 publications
14
229
2
1
Order By: Relevance
“…However, no previous isolated cell studies have shown that a 'priming' depolarization is a prerequisite for subsequent depolarization in response to hypoxia. In some studies (for example, Yuan et al 1993Yuan et al , 1994) the membrane potential in normoxic conditions was more depolarized than that observed in our study, thereby (perhaps) rendering cells sensitive to hypoxia. This difference, and the possibility that cells from different species may respond to hypoxia in a subtly different manner, could explain the discrepancy between our results and those of others.…”
Section: Synergism Between Depolarization and Hypoxiacontrasting
confidence: 53%
“…However, no previous isolated cell studies have shown that a 'priming' depolarization is a prerequisite for subsequent depolarization in response to hypoxia. In some studies (for example, Yuan et al 1993Yuan et al , 1994) the membrane potential in normoxic conditions was more depolarized than that observed in our study, thereby (perhaps) rendering cells sensitive to hypoxia. This difference, and the possibility that cells from different species may respond to hypoxia in a subtly different manner, could explain the discrepancy between our results and those of others.…”
Section: Synergism Between Depolarization and Hypoxiacontrasting
confidence: 53%
“…This effects of accompanied by an enhancement of the inward Ca 2+ current in the pulmonary artery, an effect not observed in MASMCs (Yuan et al, 1990;Yuan et al, 1993). Delayed rectifier currents that are sensitive to 4-AP are deemed to be important determinants of resting membrane potential (Em) and critical in the initiation of HPV (Post et al, 1992;Archer et al, 1998).…”
Section: Hypoxic Pulmonary Vasoconstriction (Hpv) and Chronic Hypoxicmentioning
confidence: 99%
“…Post and colleagues were the first to identify K + channel inhibition as a key event in the mechanisms of HPV via their role in membrane depolarization and subsequent opening of voltage-gated Ca 2+ channels and the promotion Ca 2+ entry (Post et al, 1992). Indeed, decreased Kv channel currents have been observed in response to acute hypoxia in both rat and mouse PASMCs (Archer et al, 1993(Archer et al, , 2001Yuan et al, 1993;Turner and Kozlowski, 1997;Platoshyn et al, 2006). Also note that Smirnov et al (1994) showed that chronic hypoxia (PO2 30-35 mmHg) causes a marked (40-50%) reduction in Kv currents amplitude, and chronically hypoxic animals have a significantly more positive (-43.5 ± 2 mV) resting membrane potential in PASMCs (Smirnov et al, 1994).…”
Section: Hypoxic Pulmonary Vasoconstriction (Hpv) and Chronic Hypoxicmentioning
confidence: 99%
“…The importance of redox processes in HIF-1 response has come to light in recent years with reports revealing that ROS may trigger HIF-la fimction (16,31,52,53,67,94,125,154). However, the role of the mitochondrial respiratory chain -one of the most well known sources of ROS -is still controversial (18,19,138,149).…”
Section: Hif-la Phosphorylation -Regulation Of Hif-1 By External Stimulimentioning
confidence: 99%
“…Also, it is possible that apoptosis in the endothelial cells is different than the apoptosis in the smooth muscle cells in the PA media. Nevertheless, Yuan et al recently showed that NO might induce PASMC apoptosis by activating Kv and KCa channels as well as depolarizing mitochondrial membrane potential (AYm) (149). The opening of sarcolemmal K* channels would cause efflux of K* and therefore osmotic cell shrinkage, which is known to initiate apoptosis; A'I'm depolarization has also been implicated in the initiation of apoptosis (29).…”
Section: Pulmonary Hypertension: Animal Models and Human Diseasementioning
confidence: 99%